Association of BK Virus Titers With Lymphocyte Count in Renal Transplant Patients - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; AKSU, MEHMET BURAK; YEGEN, ŞEVKET CUMHUR; TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2015)
Objectives. Regular screening for the BK virus (BKV) is recommended for early intervention in renal transplant patients. Identification of predictors for the development of BK viremia would improve their monitoring. We performed a retrospective study investigating whether the lymphocyte count may be a predictor of BKV development in renal transplant patients. Patients and Methods. We retrospectively analyzed 268 renal transplant patients who were followed in our clinic from January 2011 to August 2014. The viral loads of BKV in blood detected by quantitative real-time polymerase chain reaction test were performed according to relevant guidelines. We also retrospectively monitored lymphocyte count, creatinine, immunosuppressive drug doses, and tacrolimus/cyclosporine/mTor inhibitors levels during the same time as BKV screening. Demographic and other clinical data were extracted from patients' files. The calculation of correlation coefficients and receiver operating characteristics (ROC) curve analysis were performed. Results. Overall, 16 patients (5.9%) who experienced BKV-DNA positivity were included the study. Mean age of patients was 38.2 +/- 12.8 years. All patients received steroid and calcineurin inhibitors (CNIs). Mycophenolate mofetil/mycophenolic acid (MMF/MPA) was administered to 14 patients. BKV-DNA was found in 64 of the 88 (72.7%) plasma samples. The lymphocyte count on the first day of positive BKV-DNA test was significantly lower than in those with negative BKV-DNA results (1700/mu l vs 2400/mu l, respectively; P = .009). Its AUC of the ROC curve was 0.77 (P = .012). The optimal cutoff point for lymphocyte count was 1900/mu l, and sensitivity and specificity for predict BKV positivity were 75% and 78.57%, respectively. We also found that lymphocyte count negatively correlated with the first detectable BKV titers (r = -0.438; P = .015). However, there is no relation between CNI/mTOR inhibitor levels, MMF/MPA doses, lymphocyte count, and all BKV-titers. Conclusions. Decreased lymphocyte count may be a predictor for preceding BKV viremia. Clinicians should be more careful in terms of the decreased lymphocyte count in case of BKV replication in renal transplant patients.
Keywords: POLYOMAVIRUS; NEPHROPATHY; RECIPIENTS; INFECTION